Pengaruh Reward dan Punishment Terhadap Motivasi Kerja Dengan Lingkungan Kerja Sebagai Variabel Moderasi Pada Karyawan PT Equityworld Futures Surabaya - Iwanussoleh, Iwanussoleh; Faidal, Faidal (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
This study aims to analyze the influence of rewards and punishments on employee work motivation, with the work environment as a moderating variable at PT Equityworld Futures Surabaya. The method used was an associative quantitative approach, with an online questionnaire distributed to 50 respondents, representing all company employees. The analysis techniques employed included validity and reliability tests, classical assumption tests, moderated regression analysis, coefficient of determination (R²) tests, and partial t-tests. The results showed that rewards significantly influenced work motivation, while punishment did not. Furthermore, the work environment did not moderate the relationship between rewards and punishments on work motivation.